2016
DOI: 10.1038/srep30198
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Quantum Circuit in a Tunnel Junction

Abstract: Spectral analysis of 1 and 2-states per line quantum bus are normally sufficient to determine the effective Vab(N) electronic coupling between the emitter and receiver states through the bus as a function of the number N of parallel lines. When Vab(N) is difficult to determine, an Heisenberg-Rabi time dependent quantum exchange process must be triggered through the bus to capture the secular oscillation frequency Ωab(N) between those states. Two different linear and regimes are demonstrated for Ωab(N) as a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…To the large variety of systems and models described by quantum graphs belong, e.g., superconducting quantum circuits 19 , quantum circuits in tunnel junctions 20 , experimental setups to realize high-dimensional multipartite quantum states 21 , discrete-time quantum gravity models 22 and functional connectivity in preclinical Alzheimer’s disease 23 .…”
Section: Introductionmentioning
confidence: 99%
“…To the large variety of systems and models described by quantum graphs belong, e.g., superconducting quantum circuits 19 , quantum circuits in tunnel junctions 20 , experimental setups to realize high-dimensional multipartite quantum states 21 , discrete-time quantum gravity models 22 and functional connectivity in preclinical Alzheimer’s disease 23 .…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that in molecular circuits with separated parallel components, the circuit conductance could increase nonadditively due to constructive interference between the parallel paths. [ 27–31 ] Unconventional constructive QI was also predicted theoretically in single molecular electronics multi‐channels, [ 32,33 ] which has been confirmed by the experimental verdict that the conductance of quadrivial anchored molecular is about 5 times larger than that of the bidirectional one. [ 34 ] However, Hoffmann et.al indicated that the charge transport mechanism remains an open question as the electrons traveling through the multiple linkers, even though the coherent transport gives better agreement with the experimental results than that of incoherent.…”
Section: Introductionmentioning
confidence: 70%
“…Quantum graphs are the unions of vertices connected by one-dimensional quantum bounds 8 , 9 . The importance of quantum graphs stems from the fact that they can be used to describe a huge number of physical and mathematical systems and models, e.g., nanophotonic lasers on graphs 10 , superconducting quantum circuits 11 , entanglement in graph states 12 , 13 , experimental setups for high-dimensional multipartite quantum states 14 , quantum circuits in tunnel junctions 15 , and Weyl and non-Weyl quantum graphs and networks 16 .…”
Section: Introductionmentioning
confidence: 99%